Capacity Bulding Pondok Pesantren Melalui Standarisasi Laporan Keuangan Menggunakan Aplikasi Akunku - Mufarrohah, Mufarrohah; Utami, Rachma Bhakti (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2023)
Purpose – This service aims to increase the capacity of Pondok Pesantren managers in reading and compiling financial report information using the web-based “Akunku” application. Through this service activity, it is hoped that the training participants will be able to map accounts at Pondok Pesantren and compile financial reports according to Pondok Pesantren financial management standards with the help of a tool in the form of the web-based My Account application, which can present financial reports in real-time and is easily accessible from anywhere. Design/methodology/approach – This service is carried out through several stages of activity, namely (1) providing basic accounting materials, (2) journaling practices and inputting transactions through the “Akunku” application, and (3) the practice of reading financial statement information through the “Akunku” application. The stages of community service begin with the pretest and end with the posttest to determine the increase in the human resource capacity of managing Pondok Pesantren. Findings – There are 13 Pondok Pesantren assisted by Bank Indonesia, categorized as modern boarding schools. The thirteen Pondok Pesantren are categorized as modern because the activities of the students include religious education accompanied by formal education at the Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTS), Madrasah Aliyah (MA) and Higher Education levels. In addition, the thirteen Pondok Pesantren instilled an entrepreneurial spirit in the students through a business unit at the Pondok Pesantren. However, the thirteen Pondok Pesantren were constrained in compiling financial reports due to the lack of knowledge of accounting-related human resources and the absence of supporting tools in preparing financial reports. Originality/value – The posttest results show that service implementation can be effective, as shown by a better understanding than before there was capacity building. This service provides a new understanding for Pondok Pesantren managers regarding preparing financial reports for Pondok Pesantren. Preparing Pondok Pesantren financial reports using the “Akunku” application was chosen because of the ease of access from anywhere.